Sustainable Territories Adapted to the Climate: Insights from a New University Course Designed and Delivered in Guatemala - Vernooy, Ronnie; Bouroncle, Claudia; Sandoval Roque, Víctor Augusto; García, José Ramiro (MDPI, 2020)
Since 2014, the CGIAR research program on Climate Change, Agriculture and Food Security has collaborated with different stakeholders to implement climate change adaptation approaches and practices in critical locations in the Central American Dry Corridor. A new university course for professionals in the Dry Corridor aims to scale these approaches and practices. This article presents the core elements of the course, summarizes the main results, and offers recommendations for future editions. It was observed that the different trajectories and experiences of professionals facilitated a lively exchange of knowledge, the integration of local experiences in teaching, and the integration of learning in follow up proposals of governmental and non-governmental organizations. The following aspects should be central in future course editions: diversity of participants, adaptation of didactic strategies to the needs of different users, and follow-up to support, as well as the integration of course concepts and practices in the actions of different organizations. The latter requires strong organizational commitment.